VIRALITY OF MALAY LANGUAGE POSTINGS ON FACEBOOK: AN ANALYSIS ON CONTENT AND LINGUISTICS ATTRIBUTES - NINIEFADZILLEA, ISWANDI (Universiti Malaysia Sarawak (UNIMAS), 2020)
The increasing use of Facebook among users from different walks of life has made it one of the main sources of information. The extra attention given to these Facebook posts has created a phenomenon known as “virality” in which a post can be shared to hundred thousand of users within a short time, way faster than the mainstream media. While previous studies have investigated viral postings from the perspective of business and mostly in English posts, this study aims to linguistically analyse the Malay language postings on Facebook that causes them to be viral in terms of content and linguistics attributes. Using textual analysis of 100 Facebook postings from various topics that went viral with a corpus size of about 10,000 words, this study captured the content and language attributes of each post and tabulate them accordingly. The results showed that the main content attribute of viral postings is largely related to family-related advices while the most common linguistic features are the use of personal pronouns as well as high occurrences of adjectives. In terms of writing styles, it was found that arguments/debate and anecdote are the most popular. The findings from this study have provided valuable input to social media marketers in creating content that would reach out to more users. Future research, however, can increase the scope of viral postings by increasing the number of sample and also correlate with other demographic factors.